Sistem Informasi Kinerja Pengelolaan Penghasilan Asli Daerah Dan Tingkat Kemandirian Pemerintah Kota Ternate Provinsi Maluku Utara - Muhdar Abdurahman - Politeknik Sains dan Teknologi Wiratama Maluku Utara (Indonesian Journal of Networking and Security (IJNS), 2016)
Abstract - Information Systems Managemen Performance Orginal Regional Income and Level Of Independence Of Government of Ternate of North Maluku Province This research aims to know the performance of financial management Local Revenues (PAD) using financial ratio in Ternate City budget based on the analysis of the System Information. Research variables to know the performance of the System Analysis of the regional financial management information and the level of independence of the Government of the City of Ternate. Data Analysis methods used in this research is the method of calculation of the ratio of the independence of the regional keuangn. This research is to evaluate directly against the data that consists of primary data and secondary data, covers Sisdur, Organizational Structure and the document is used, with how to approach on the stakeholders, especially parties that have an interest in the tax information system. The discussion of the results of this research also discussed about how the implementation of Information System performance of regional financial management, how the implementation of the Information System of the original regional income (SIMPADA) level as well as the independence of the Government of the City of Ternate budget year 2011-2015. Based on the analysis of the system information and the discussion of the yan gtelah outlined, the average responding to performance and financial independence of the city of Tenate level in the era of regional autonomy based on the analysis of the financial ratio is good. Seen from the level of the ratio of the regional financial independence Town Ternate is instructive because it has an average of 18,76%(